The ubiquitin ligase dTopors directs the nuclear organization of a chromatin insulator. - Capelson, M.; Corces, V.G. (Molecular Cell, 2005)
Chromatin insulators are gene regulatory elements implicated in the establishment of independent chromatin domains. The gypsy insulator of D. melanogaster confers its activity through a protein complex that consists of three known components, Su(Hw), Mod(mdg4)2.2, and CP190. We have identified a factor, Drosophila Topoisomerase I-interacting RS protein (dTopors) that interacts with the insulator protein complex and is required for gypsy insulator function. In the absence of Mod(mdg4)2.2, nuclear clustering of insulator complexes is disrupted and insulator activity is compromised. Overexpression of dTopors in the mod(mdg4)2.2 null mutant rescues insulator activity and restores the formation of nuclear insulator bodies. dTopors associates with the nuclear lamina, and mutations in lamin disrupt dTopors localization as well as nuclear organization and activity of the gypsy insulator. Thus, dTopors appears to be involved in the establishment of chromatin organization through its ability to mediate the association of insulator complexes with a fixed nuclear substrate.